EFFECT OF ETHANOL EXTRACT GENDOLA LEAF LEAF (Basella alba L.) ON DECREASING BLOOD GLUCOSE CONDITION AND HISTOPATOLOGY PANKREAS WHITE RATS (Rattus norvegicus) INDICATED STREPTOZOTOCIN - Joni Tandi (JIMR - Journal of Islamic Medicine Research, 2017)
This study aims to examine the content of secondary metabolites in red gendola leaf ethanol extract, the effect of ethanol extract of leaf of red gendola on decreasing in blood glucose levels, the effect of graded doses to decrease blood glucose levels and show illustration histopathology pancreas of the rats induced diabetes mellitus streptozotocin. The research was a laboratory experiment using a modified posttest study design randomized controlled groups design. A total of 24 rats were divided into six groups, each group consisted of four rats with details of group I, II, and III as a control group, and groups IV, V, and VI as the experimental group. Group I: normal control given CMC Na 0,5%; Group II: negative controls were given CMC Na 0,5% and streptozotocin induced 40 mg/kg intraperitoneally rats; Group III: positive controls were given a dose of glibenclamide 0.45 mg/kg and streptozotocin induced 40 mg/kg intraperitoneally rats; each experimental group was given ethanol extract of leaf of red gendola at a dose of 100 mg/kg, 200 mg/kg, 400 mg/kg and streptozotocin induced 40 mg/kg of rat intraperitoneally.The results show that: there are secondary metabolites in red gendola leaf ethanol extract namely alkaloids, flavonoids, tannins, saponins and phenols ; the ethanol extract of leaf of red gendola at a dose of 100 mg/kg effective in lowering blood glucose levels in male rats and at a dose of 400 mg / kg effective in regenerating pancreatic tissue; ethanol extract of leaf of red gendola dose of 200 mg/kg and 400 mg/kg did not give full effect to the decrease in blood glucose levels in male rats and ethanol extract of leaf of red gendola at doses of 100 and 200 mg / kg did not give full effect to the regeneration of pancreatic tissue streptozotocin-induced rats induced streptozotocin. Keywords: Streptozotocin, gendola red (Basella alba L.), blood glucose levels, histopathology pancreas.